The egg hatch test: A useful tool for albendazole resistance diagnosis in Fasciola hepatica. - Ceballos, L. (2019)
In the current study, the egg hatch test (EHT) has been evaluated as an in vitro technique to detect albendazole (ABZ) resistance in Fasciola hepatica. The intra- and inter-assay variations of the EHT were measured by means of the coefficient of variation in different fluke isolates and over time; then, the results of the EHT were compared with the "gold standard" controlled efficacy test, which assesses the in vivo anthelmintic efficacy. The EHT was used later to evaluate the intra-herd variability regarding the level of ABZ resistance in calves infected by the same fluke isolate. Finally, several factors of the initial protocol were modified to improve the simplicity of the assay, including the incubation time of eggs with the drug and the use of eggs collected from faeces. The greatest uniformity between results within the assay and over time until 8 weeks after gallbladder collection (the deadline proposed for egg analysis) was obtained with an ABZ concentration of 0.5 μM. The length of exposure to ABZ was shown to be critical, as prolonged incubation (15 days) led to a change of ovicidal activity. The ABZ concentration of 0.5 μM is suggested as a possible discriminating dose to predict ABZ resistance, due to the close agreement between the results of the EHT at an ABZ concentration of 0.5 μM and those of the in vivo assays.